A Brief Description of ?Inqalab Mung? Mungbean (Vigna radiata L. Wilczek) Variety Released for the Agro-Climatic Conditions of Khyber Pakhtunkhwa, Pakistan: Mangbean Variety from KPK - Mansoor, Muhammad; ullah, Aman; Latif, Noman; Hussain, Nazir; Majeed, Abdul (Biological Sciences - PJSIR, 2018)